2016
DOI: 10.3201/eid2209.160304
|View full text |Cite
|
Sign up to set email alerts
|

EnterohemorrhagicEscherichia coliHybrid Pathotype O80:H2 as a New Therapeutic Challenge

Abstract: This emerging clonal group harbors the extraintestinal virulence–associated plasmid pS88 and can induce invasive infections and death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 79 publications
(113 citation statements)
references
References 37 publications
(54 reference statements)
1
112
0
Order By: Relevance
“…Moreover, the Stx2 d gene is known to cause a more severe course of disease. This together with the rare eae ξ and the plasmid of the O80:H2 STEC, which showed high resemblance with the previous described plasmid associated with extra intestinal virulence, resulted in an increased association with HUS [8]. Only recently, Soysal et al described the STEC serotype O80 as a new therapeutic challenge in patients with STEC-HUS due to its capacity to cause a bacteremia [8].…”
Section: Discussionmentioning
confidence: 81%
“…Moreover, the Stx2 d gene is known to cause a more severe course of disease. This together with the rare eae ξ and the plasmid of the O80:H2 STEC, which showed high resemblance with the previous described plasmid associated with extra intestinal virulence, resulted in an increased association with HUS [8]. Only recently, Soysal et al described the STEC serotype O80 as a new therapeutic challenge in patients with STEC-HUS due to its capacity to cause a bacteremia [8].…”
Section: Discussionmentioning
confidence: 81%
“…Another antibiotic‐resistant hybrid STEC serotype, O80:H2, was isolated in France from 54 patients between 2005 and 2014 (Soysal et al, ). These STEC isolates were found to carry several variants of the stx2 gene, a rare variant of the intimin gene (eae‐ξ) and genetic determinants related to the pS88 plasmid associated with extraintestinal‐virulence pathogenic E. coli (ExPEC), avian pathogenic E. coli (APEC) and E. coli strains that cause neonatal meningitis (NMEC; Soysal et al, ).…”
Section: Emerging Ar‐stec Strainsmentioning
confidence: 99%
“…Another antibiotic‐resistant hybrid STEC serotype, O80:H2, was isolated in France from 54 patients between 2005 and 2014 (Soysal et al, ). These STEC isolates were found to carry several variants of the stx2 gene, a rare variant of the intimin gene (eae‐ξ) and genetic determinants related to the pS88 plasmid associated with extraintestinal‐virulence pathogenic E. coli (ExPEC), avian pathogenic E. coli (APEC) and E. coli strains that cause neonatal meningitis (NMEC; Soysal et al, ). Although STEC O80:H2 was found to be resistant to amoxicillin, nalidixic acid, cotrimoxazole and kanamycin with 52% of the isolates being resistant to all four antibiotics, subsequent in vitro studies demonstrated that this STEC was susceptible to azithromycin with no induction of Stx suggesting that this antibiotic could probably have been used to effectively treat patients (Soysal et al, ).…”
Section: Emerging Ar‐stec Strainsmentioning
confidence: 99%
See 2 more Smart Citations